Iodine‐Catalysed Synthesis of β‐Carboline Tethered α‐Amino Amidines Through Ugi‐Type Multicomponent Reaction. Issue 35 (15th September 2022) - Singh, Manpreet; Vaishali,; Jamra, Rahul; Deepika,; Kumar, Sunit; Singh, Virender
Abstract: A simple and efficient iodine catalysed protocol has been unfolded for the synthesis of novel β‐carboline C1‐linked α‐amino amidines via one‐pot assembly of 1‐formyl β‐carbolines (Kumujian C analogues), anilines and isocyanides. This domino strategy proceeds through the formation of three C−N bonds in a single operation. The advantageous features of the developed methodology include one‐pot synthesis, operational simplicity, high atom economy, broad substrate scope, multicomponent character, easy purification procedure (no column chromatography) and applicability towards gram scale synthesis. The scope of strategy has been demonstrated with the construction of a library of 32 novel β‐carboline tethered α‐amino amidines having three points of diversity. Abstract : A transition metal‐free gram‐scale strategy has been formulated to access novel β‐carboline linked α‐amino amidines via the formation of three C−N bonds in single operation. The strategy is found compatible with gram‐scale synthesis also.